Modelling the Effects of Cranial Cruciate Ligament Transection, Medial Meniscal Release and Triple Tibial Osteotomy on Stability of the Canine Stifle Joint - Jensen, Tanja V.; Kristiansen, Signe S.; Buelund, Lene E.; Miles, James E. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of this study was to evaluate the ex vivo effects of sequential cranial cruciate ligament transection (CCLx), medial meniscal release (MMR) and triple tibial osteotomy (TTO) on canine stifle stability compared with the intact state, across a wide range of joint angles.Study Design Nine right hind limb preparations were instrumented to provide constant quadriceps and gastrocnemius loads in a 3:1 ratio, and extended from full flexion during fluoroscopic recording. Recordings were repeated after each of CCLx, MMR and TTO. Fluoroscopic landmarks were used to calculate tibial subluxation and patellar ligament angle.Results Medial meniscal release resulted in additional cranial tibial subluxation compared with CCLx. Triple tibial osteotomy restored stifle stability up to a joint angle of 125 degrees. The presence of the crossover angle could be inferred from the patellar ligament angle and subluxation curves.Conclusion Our results suggest that in the cranial cruciate ligament-deficient stifle, the crossover angle at which loading shifts between the caudal and cranial cruciate ligaments is dependent on both loading and integrity of the medial meniscus. Triple tibial osteotomy improves stifle stability over a wide range of joint angles under a quadricep to gastrocnemius loading ratio of 3:1 by converting cranial tibial thrust to caudal tibial thrust, due to TTO increasing the amount of joint extension required to reach the crossover angle.
Keywords: stifle joint; cranial cruciate ligament; triple tibial osteotomy; stifle model; meniscal release; stability